Soluble triggering receptor expressed on myeloid cells‐1 is a biomarker of anti‐CCP‐positive, early rheumatoid arthritis. (24th April 2015) - Molad, Yair; Ofer‐Shiber, Shachaf; Pokroy‐Shapira, Elisheva; Oren, Shirly; Shay‐Aharoni, Hagit; Babai, Ilan
Abstract Objectives To assess serum soluble triggering receptor expressed on myeloid cells‐1 (sTREM‐1) levels in disease‐modifying antirheumatic drug (DMARD)‐naïve early rheumatoid arthritis (ERA), to investigate the association of sTREM‐1 levels with Disease Activity Score in 28 joints (DAS28) and seropositivity for anti‐cyclic citrullinated peptide (CCP) antibody and to determine the predictive value of sTREM‐1 with respect to clinical response to DMARD therapy. Methods Twenty‐two consecutive patients with DMARD‐naïve ERA were prospectively evaluated for serum sTREM‐1 by means of ELISA at diagnosis and at the following clinic visit after prednisone and/or DMARD has been administered, and related to DAS28 and serum level of anti‐CCP antibody. We compared the sTREM‐1 level to that of 31 patients with established RA as well as to 24 controls. Results Serum sTREM‐1 level was significantly higher in the DMARD‐naïve ERA group (2122·9 ± 388·9 ρg/mL) compared to established RA group (1478·0 ± 280·0 ρg/mL, P = 0·001) and normal control (34·4 ± 7·4 ρg/mL, P < 0·001). In the ERA group, elevated basal sTREM‐1 level correlated with higher DAS28‐CRP score (P = 0·001, HR 3·23, 95% CI 1·4–8·12), DAS28‐ESR (P = 0·04, HR 2·34 95% CI 0·1–8·12), as well as predicted higher DAS28 score at the following encounter after DMARD treatment was administered (P = 0·001, HR 3·2 95% CI 1·1–7·2). Higher serum level of sTREM‐1 correlated with higher titres of anti‐CCP antibody (P < 0·001). Conclusions Our results suggest that serum sTREM‐1 may provide a novel biomarker for DMARD‐naïve ERA as well as for seropositivity for anti‐CCP antibody and RA activity.